2020
DOI: 10.1155/2020/1325071
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Reconstruction of IMFs of Decomposition and Ensemble Model for Forecasting Crude Oil Prices

Abstract: Accurate forecasting for the crude oil price is important for government agencies, investors, and researchers. To cope with this issue, in this paper, a new paradigm is designed for the reconstruction of intrinsic mode functions (IMFs) of decomposition and ensemble models to reduce the complexity in computation and to enhance the forecasting accuracy. Decomposition and ensemble methodologies significantly enhance the forecasting accuracy under the framework of “divide and conquer” with the proposed reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…us, for forecasting the crude oil prices, the MEEMD is recommended for data decomposition. e model MEEMD-GMDH outperforms all of the models for a different number of observations, that is, 500, 1000, 2000, 5000, and 10000. e MAPE values of the model MEEMD-GMDH are less than 1 for all sets of observations which demonstrated the highly accurate forecasts [37,38]. e experimental findings of both scenarios demonstrated that all ensemble methodologies were effective but MEEMD was more effective.…”
Section: Monte Carlo Simulationsmentioning
confidence: 91%
See 1 more Smart Citation
“…us, for forecasting the crude oil prices, the MEEMD is recommended for data decomposition. e model MEEMD-GMDH outperforms all of the models for a different number of observations, that is, 500, 1000, 2000, 5000, and 10000. e MAPE values of the model MEEMD-GMDH are less than 1 for all sets of observations which demonstrated the highly accurate forecasts [37,38]. e experimental findings of both scenarios demonstrated that all ensemble methodologies were effective but MEEMD was more effective.…”
Section: Monte Carlo Simulationsmentioning
confidence: 91%
“…e MEEMD and EEMD procedure divided the original time series into IMFs in such a way that the first IMF is more stochastic as compared to the second IMF and the second IMF is more stochastic than the third IMF and so on, whereas the last IMF is completely deterministic. Synthetic time series datasets which are composed of additive white noise and sine function are described in two different scenarios as follows [37][38][39]:…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…After modifying the number of nodes, the number of layers, and the activation function of the intermediate hidden layer, we use the framework provided by Tensorflow for training and select a model with low resource consumption and high accuracy. Regarding the setting of the number of hidden layers, we refer to the paper proposed by Xu et al [15] in 2020.…”
Section: Model Architecturementioning
confidence: 99%
“…The authors in (Zhang et al 1998) used two hidden layers and finds better model prediction accuracy. In the same way, the authors in (Xu et al 2020) used (2 × 𝑘 + 1), where 𝑘 is the number of predictors (inputs). For an optimal result of ANN, usually, trial and error method is used in determining the number of hidden nodes i.e.…”
Section: Autoregressive Distributive Lag Modelsmentioning
confidence: 99%